Effects of Awareness Programs on Juvenile Delinquency: a Three-Level Meta-Analysis - Put van der, Claudia E. (International journal of offender therapy and comparative criminology, 2021)
Juvenile awareness programs, such as Scared Straight, remain in use despite the finding that these programs provoke rather than prevent delinquency. The aim of this study was to examine what program components are associated with program effectiveness, which is important for improving these programs. A three-level meta-analysis was conducted. A literature search yielded 13 independent studies (N = 1,536) from which 88 effect sizes could be extracted. A nonsignificant overall effect was found (d = 0.10), indicating that juvenile awareness programs have no effect on offending behavior and other outcomes that are related to delinquency. No significant moderator effects were found for program components. The moderator analyses revealed that juvenile awareness programs are effective in reducing antisocial attitudes (d = 0.46), which has not been meta-analytically studied before. Furthermore, larger effects were found as follow-up length increased. These results show a more nuanced view on the effectiveness of juvenile awareness programs is necessary.